Representation of themes from sociology of in Sociološki pregled / Sociological review (1938-2017) - Košarac, Biserka R.; Ćorluka, Bojan (Sociološki pregled, 2018)
In this paper the authors provide a synthetic review and analysis of the papers from the feld of Sociology of family in Sociološki pregled/ Sociological Review (1938–2017). The research of family in the Balkans region has a long-lasting tradition and even in the frst publications of Sociološki pregled/ Sociological Review themes regarding the sociology of family had been presented. In the published papers we can see the very presence of the historical continuity of existence and disappearance of family cooperative and traditional, patriarchal family and formation of its modern models. Also, the papers follow changes the family passed through in the period afer 1990s, putting stress on almost every single aspect of a family: structure, functions, family relations, family pathology, socialisation of children, parenthood and appearance of new, alternative forms of marriage and family.